Leukemic Cell Lysis by Activated Human Macrophages: Significance of Membrane‐associated Tumor Necrosis Factor - Nakabo, Yukiharu (Jpn J Cancer Res, 1993)
In this study, we analyzed the mechanism(s) of leukemic cell lysis by human macrophages. Peripheral blood monocyte‐derived macrophages were activated with recombinant interferon‐γ and lipopoly‐saccharide and their lytic activity against two leukemic cell lines (K562 and HL‐60 cells) was assessed by an (111)In releasing assay. Activated macrophages lysed these leukemic cells, and the lytic activity against leukemic cells was almost completely inhibited by anti‐tumor necrosis factor (TNF) antibody. The macrophage‐lysate prepared from activated macrophages also exhibited significant lytic activity against leukemic cells; this lytic activity was inhibited by anti‐TNF antibody. The leukemic cells that we used for the cytotoxicity assays were resistant to recombinant TNF. The culture supernatant of activated macrophages did not show any lytic activity. These findings suggest that cell‐associated TNF plays a role in macrophage‐mediated cytotoxicity against leukemic cells.